PERANCANGAN PROTOTYPE LAMPU RUMAH TANGGA VIA WIRELESS BLUETOOTH 2,4 GHZ BERBASIS ARDUINO - Agus Sumarjono (Faculty of Industrial Technology Universitas Islam Indonesia, 2018)
Wireless communication technology or generally called as Wireless Technology (Teknologi Nirkabel) is considered as efficient technology in terms of cost and the usage. The home lighting controller by wireless with bluetooth technology module HC-05 using radio frequency 2,4 GHz is a system that are designed to ease the operator or user in controlling home lighting remotely by using bluetooth technology with Arduino microcontroller as its controller system programming as well as using smartphone as the remote control. The design of this prototype covers several stages : 1. Requirement Identification, 2. Requirement Analysis, 3. Tools’ design (Proteus Simulation), 4. Tools’ development (Hardware), 5. Controller Programming (Arduino Software), 6. Prototype, 7. Testing. From the result of the method, it can be resumed that the Home Lighting Controller via Wireless Bluetooth 2,4 GHz based on Arduino could simplify operator or user in turning the lights (ON – OFF) wirelessly. Besides it also can be exposed as an introduction and learning media for basic knowledge on Electrical Engineering in terms of Telecommunication at the Basic Electrical Engineering Laboratory, Faculty of Industrial Technology, Universitas Islam Indonesia, Yogyakarta.